Analysing risk factors for foetal growth outcomes - the influence of maternal conditions and congenital cytomegalovirus infection - Mandžáková, Miroslava; Záhumenský, Jozef; Vajdová, Eva; Matušíková, Zuzana; Rosoľanková, Monika; Papcun, Peter (Ceska gynekologie, 2025)
OBJECTIVE: This study aimed to analyse the risk factors differentiating small for gestational age (SGA) and appropriate for gestational age (AGA) neonates. MATERIALS AND METHODS: A retrospective-prospective cohort study was conducted from 2019 to 2024 at the 2nd Department of Obstetrics and Gynaecology, University Hospital Bratislava. The study involved 174 term neonates from singleton pregnancies, including 125 SGA and 49 AGA infants. Various maternal, foetal, and placental risk factors were analysed, with a particular focus on congenital cytomegalovirus infection (cCMV). RESULTS: Neonates' birth weights ranged from 1,480 to 4,470 grams. Of the risk factors assessed, only maternal COVID-19 infection during pregnancy was significantly associated with AGA outcomes (P = 0.009). No significant associations were found between common risk factors (e. g. hypertension, diabetes mellitus) and foetal growth restriction. Congenital CMV infection was not significantly associated with SGA. Logistic regression analysis confirmed the association of COVID-19 infection with foetal weight, while no significant effect was observed for CMV. CONCLUSION: Maternal COVID-19 infection was associated with AGA outcomes, potentially due to enhanced medical surveillance and immune responses. However, the study's small sample size limits the interpretation of these findings, and further research is required to fully understand the impacts of COVID-19 on pregnancy. No significant association between congenital CMV infection and foetal growth restriction was found in this cohort, which was most likely due to the low prevalence of cCMV. Moreover, documented risk factors for foetal growth restriction, including hypertension and diabetes mellitus, were not statistically significant in our study population.
Keywords: těhotenství; Cytomegalovirus Infections; COVID-19; congenital cytomegalovirus infection; lidé; Adult; cytomegalovirové infekce; růstová retardace plodu; infekční komplikace v těhotenství; porodní hmotnost; Risk Factors; doppler ultrasound of uterine artery; prospektivní studie; Fetal Growth Retardation; Female; retrospektivní studie; Infant, Small for Gestational Age; small for gestational age; Humans; Infant, Newborn; Prospective Studies; Pregnancy Complications, Infectious; appropriate for gestational age; hypotrofický novorozenec; novorozenec; foetal growth restriction; Pregnancy; ženské pohlaví; risk factors; clinical characteristics; Retrospective Studies; perinatal outcomes in COVID-19 pregnancies; dospělí; Birth Weight; rizikové faktory